Production and Characterization of Polyurethane-Based Artificial Leather Using Release Paper Technology - Siddhi Shukla; Rajesh Kumar Kaushal; Vikas Vishwakarma (UPT Laboratorium Terpadu, Universitas Diponegoro, 2026)
Natural leather production involves animal use and chemical-intensive tanning processes, creating environmental and ethical concerns. Therefore, developing sustainable alternatives is important for modern footwear, garment, furniture, and automotive industries. This study aimed to prepare polyurethane (PU)-based synthetic leather using release paper technology and evaluate its physical and mechanical properties. PU solution was coated onto textured release paper, followed by drying, curing, and lamination with textile fabric to obtain the final leather-like material. The prepared product successfully reproduced a leather-like surface texture. Mechanical testing revealed tensile strength values of 11–18 MPa and elongation at break of 180–300%, indicating adequate strength, flexibility, and durability for practical applications. The process also offers advantages such as lower volatile organic compound emissions, avoidance of chromium-based tanning chemicals, and potential reuse of release paper. These findings demonstrate that PU-based synthetic leather produced by this method is a promising alternative to conventional natural leather. The developed material demonstrates potential for sustainable industrial synthetic leather production. Copyright © 2026 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).